Evaluasi Sistem Elektronik Rekam Medis di Rumah Sakit Primasatya Husada Citra Surabaya - Hayu Ning Widyastuti; Dony Setiawan Hendyca Putra; Efri Tri Ardianto (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
One of the obligations of the hospital is carrying out medical records. The implementation of medicalrecords at the Primasatya Husada Citra Surabaya Hospital has used an electronic system. The applicationis an Electronic Medical Record (ERM) with a website-based that runs since September 1, 2018. SinceSeptember 1, 2018, until now there has never been an evaluation of the application. This study aims toevaluate ERM using the Human Organization Technology (HOT) -Fit Model evaluation method. This typeof research is qualitative research with data collection methods using interviews, observation, anddocumentation. The results of the study indicated that the implementation of ERM has been going well,socialization and training have been provided by organizations, the presentation of data are not right, andcomputer facilities are still lacking. The researcher's suggestion for ERM at PHC Surabaya Hospital is totest the reliability and security of the ERM system, add one computing device, and improve thepresentation of data by the system to improve the quality of the ERM system.